2007
DOI: 10.1016/s1130-6343(07)75374-6
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de las causas y factores predictivos de discontinuación del tratamiento con tenofovir en pacientes VIH pretratados

Abstract: Almost a quarter of the patients discontinued treatment with tenofovir during the study. The main cause for this was adverse effects. No association was found between any abnormal basal analytical parameter and a greater probability of discontinuing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Researchers demonstrated that patients with HIV under pharmaceutical care have significantly improved CD4+ counts, decreased HIV viral load, and fewer toxic effects related to ARV drugs 39. Toxicity reduction improves patient quality of life and treatment adherence 4042. A cohort study in 2,234 patients showed that those patients who had pharmacy team involvement in their care adhered more to ARV therapy than those who did not have pharmacy team involvement 43.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers demonstrated that patients with HIV under pharmaceutical care have significantly improved CD4+ counts, decreased HIV viral load, and fewer toxic effects related to ARV drugs 39. Toxicity reduction improves patient quality of life and treatment adherence 4042. A cohort study in 2,234 patients showed that those patients who had pharmacy team involvement in their care adhered more to ARV therapy than those who did not have pharmacy team involvement 43.…”
Section: Discussionmentioning
confidence: 99%
“…The exact reason for this finding was unclear and will require further research. However, a study that investigated causes for discontinuing treatment amongst patients on TDF, reported that about 23.8% of patients on TDF in that study population discontinued therapy due mainly to adverse reaction [29]. Another study in South Africa reported that patients with preexisting mild to moderate renal dysfunction were at greatest risk of death [30].…”
Section: Discussionmentioning
confidence: 99%
“…Su incidencia puede variar entre el 1% y el 30% de acuerdo con la metodología empleada para su detección y evaluación. Los problemas de seguridad y costo de estas cuando son graves tienen un peso considerable en los sistemas de salud, pues se dice que son responsables de más de 770.000 lesiones y muertes anuales a nivel mundial, y que ocasionan hasta 56 millones de dólares de gasto por hospital -dependiendo del tamaño del mismo 3,7,8 .…”
Section: Introductionunclassified